A fabulosa máquina de assistir: a interface web e as novas formas de fruição do audiovisual - Cunha, Cláudio Ribeiro da (2009)
This paper presents the creation of a website, configured as an interface, based on the technological structure of web, in the combination of sounds, images and texts, for access to a repertoire of fragments of representative parts of the audiovisual language, in its diverse manifestations - cinema, television, video and computer. One is about a proposal of enjoyment of audiovisuals parts that, placed in an environment web, can be attended in lot, that is, some touched simultaneously, had access and combined parts in random way. Inspired in the work of Lucia Santaella - Matrizes da Linguagem e do Pensamento: sonora, visual, verbal: aplicações na hipermídia (São Paulo: Fapesp; Iluminuras, 2005) - we use the idea of the three matrices as the base that organizes the relationship of the interator with the interface. It is possible, for example, to try different sonorous tracks in one same stretch of film or some simultaneous stretches, to feel as this affects our perception. Finally, the verbal matrix if integrates to our interface of some forms. First, as the organized element of the website, composing the menu of options that are had access through hyperlinks. In according to place, as constituent element of the proper presented audiovisuals parts, or you say through them or through the word written incorporated to the video. Finally, we organize a set of texts that supply information to contextualize each workmanship